Keragaan Penawaran dan Permintaan Beras di Indonesia - Desi Aryani (Seminar Nasional Lahan Suboptimal, 2018)
Aryani et al, 2019. Rice Supply and Demand in Indonesia. pp. 287-297. Indonesian residents have a high dependence on consuming rice as the main staple food. This paper aimed to analyze the performance of the development of rice supply and demand in Indonesia. The data used are annual secondary data from 2000 to 2015. Data is sourced from the Central Bureau of Statistics, National Bureau of Logistics, and the Ministry of Trade. The performance of the supply and demand of Indonesian rice during the period 2000 to 2015 shows an increasing trend with a balance of surplus. The main component that forms the supply of Indonesian rice consists of total rice production, initial period rice stocks, and imports. While the main component forming the demand for rice can be defined as the total consumption of rice, the end of the period rice stock, and exports. In 2015 Indonesia's total rice production was 47,304,605 tons with production centers concentrated in Java, namely East Java, West Java and Central Java. In the same year, total consumption was 33,144,541 tons so that the surplus of Indonesian rice was 15,316,264 tons.